2004
DOI: 10.1161/01.hyp.0000111829.46090.92
|View full text |Cite
|
Sign up to set email alerts
|

Increased Central Artery Stiffness in Impaired Glucose Metabolism and Type 2 Diabetes

Abstract: Abstract-Impaired glucose metabolism (IGM) and type 2 diabetes (DM-2) are associated with high cardiovascular disease risk. Increases in peripheral and central artery stiffness may represent pathophysiologic pathways through which glucose tolerance status leads to cardiovascular disease. Peripheral artery stiffness increases with deteriorating glucose tolerance status, whereas this trend remains unclear for central artery stiffness. Therefore, we investigated the associations between glucose tolerance status a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
302
7
28

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(353 citation statements)
references
References 39 publications
16
302
7
28
Order By: Relevance
“…20) The Hoorn Study revealed that subjects with impaired glucose tolerance and DM had arterial stiffening in both the central and peripheral arterial system using applanation tonometry and that the central arterial stiffness of those with impaired glucose tolerance was intermediate in severity between the group with normal glucose tolerance and DM. 21) In our current study, we also observed that pre-DM patients have statistically significantly higher SI and lower CI than those without DM. SI, derived from the DVP measured by photoplethysmography, is a valid index of wave refl ections and also an acceptable marker for large artery stiffness.…”
Section: Discussionsupporting
confidence: 77%
“…20) The Hoorn Study revealed that subjects with impaired glucose tolerance and DM had arterial stiffening in both the central and peripheral arterial system using applanation tonometry and that the central arterial stiffness of those with impaired glucose tolerance was intermediate in severity between the group with normal glucose tolerance and DM. 21) In our current study, we also observed that pre-DM patients have statistically significantly higher SI and lower CI than those without DM. SI, derived from the DVP measured by photoplethysmography, is a valid index of wave refl ections and also an acceptable marker for large artery stiffness.…”
Section: Discussionsupporting
confidence: 77%
“…The study population for this investigation therefore consisted of 466 individuals except for the analyses of the carotidfemoral transit time, which was available in only 193 individuals. 33 …”
Section: Resultsmentioning
confidence: 99%
“…The estimates of artery stiffness were determined as described earlier with the use of arterial ultrasonography, echocardiography and radial applanation tonometry 28,32,33 according to the following: distensibility-an indicator of local arterial elastic properties: ((2DD Â D þ DD 2 )/(DP Â D 2 ) in 10 À3 kPa À1 ; compliance-an indicator of local arterial buffering capacity: p(2D Â DD þ DD 2 )/(4 Â DP) in mm 2 kPa À1 ; Young's elastic modulus-an indicator of local intrinsic elastic wall properties: (D/(IMT) Â distensibility) in kPa (where DP stands for local pulse pressure, 34,35 D for diameter, (DD) for distension and IMT for carotid intima-media thickness); total systemic arterial compliance-an indicator of total arterial buffering capacity-by the exponentialdecay method based on the Windkessel model 36 and the ratio of stroke volume to aortic pulse pressure; 37 aortic augmentation index-an indicator of total stiffness and wave reflection-by the use of a generalized transfer function; 38 and carotid-femoral transit time-an estimate of regional stiffness closely associated with the gold standard estimate of stiffness: pulse wave velocity-by the time delay from the electrocardiograph trigger to 10% of the ascending slope of the distension curve of both arteries subtracted from one another. 39 …”
Section: Arterial Stiffnessmentioning
confidence: 99%
“…Premature conduit vessel arteriosclerosis predicts mortality in type 2 diabetes [3] and may be attenuated by therapeutic approaches with potential to lower glucose or blood pressure directly [4][5][6][7]. The independent association of FPG and 2-HPG indices with the haemodynamic consequence of early sclerosis (aortic stiffness) implies that modifiable structural mechanisms connect hyperglycaemia with vascular complications even within prediabetes thresholds of impaired glucose tolerance (IGT) [8][9][10][11] and impaired fasting glycaemia (IFG) [12,13]. These relationships are reported individually [11][12][13] or as a cumulative effect of the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%